Imaging: PEGylated Luminescent Gold Nanoclusters: Synthesis, Characterization, Bioconjugation, and Application to One‐ and Two‐Photon Cellular Imaging (Part. Part. Syst. Charact. 5/2013). (28th May 2013) - Oh, Eunkeu; Fatemi, Fredrik K.; Currie, Marc; Delehanty, James B.; Pons, Thomas; Fragola, Alexandra; Lévêque‐Fort, Sandrine; Goswami, Ramasis; Susumu, Kimihiro; Huston, Alan L.; Medintz, Igor L.
<x xml:space="preserve">Abstract</x> Biocompatible, near‐infrared luminescent gold nanoclusters (AuNCs) are synthesized directly in water using PEG‐dithiolane ligands terminating in either a carboxyl, amine, azide or methoxy group as presented by Igor L. Medintz and co‐workers on page 453. Following bioconjugation testing, stability assays, and extensive characterization of their one‐ and two‐photon absorption cross‐section and emission, the AuNCs are demonstrated in high signal‐to‐noise one‐ and two‐photon cellular imaging with mini mal cytoxicity. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>